TSAKA happiness : leveraging granny's botanical recipes to create an organic, vegan beauty brand - O'Brien, Justin, (SAGE business cases., 2022)
When the cold British climate started to take a toll on Celmira Amade's melanin-rich skin (non-Caucasian), and she was unable to find the right products in the high street stores to help fix her blemishes, dryness, and uneven tone, she decided to act. Inspired by her grandmother's traditional, organic beauty recipes, the idea for the vegan skincare brand TSAKA was born. After delivery and production problems limited her face mask sales, customers started to express far greater interest for Celmira's hair recipes. Students will be asked to consider if Celmira should pivot her business so as to focus on another product.